1984
DOI: 10.1039/dt9840001667
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies of a range of stannane radical cations

Abstract: Exposure of dilute solutions of stannanes in freon (CFCI,) at 77 K to 6oCo y-rays gave the parent radical cations. SnH, gave two well defined centres, both exhibiting very large hyperfine coupling to l17Sn and 119Sn. One, with CgV symmetry, showing strong coupling to a unique proton, is thought to have the unpaired electron confined to one Q Sn-H orbital with a large 5s contribution from tin. The other (C2" symmetry), with strong coupling to two equivalent protons, and formed initially in almost equal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…The occurrence of photostimulated reaction (2) (or similar thermally stimulated process upon heating the sample from 77 to 120 K) followed by reaction (3) makes it possible to explain apparent contradiction between the data reported by Walther et al [11] and those presented by Symons [9] and Hasegawa et al [10]. Indeed, matrix radical ions (whose reactions could lead to the generation of [(ëç 3 ) 4 ]~ followed by formation of methyl radicals) in SiCl 4 or CFCl 3 matrices containing Me 4 radical cations were preliminarily bleached in [11] and not bleached in [9,10].…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The occurrence of photostimulated reaction (2) (or similar thermally stimulated process upon heating the sample from 77 to 120 K) followed by reaction (3) makes it possible to explain apparent contradiction between the data reported by Walther et al [11] and those presented by Symons [9] and Hasegawa et al [10]. Indeed, matrix radical ions (whose reactions could lead to the generation of [(ëç 3 ) 4 ]~ followed by formation of methyl radicals) in SiCl 4 or CFCl 3 matrices containing Me 4 radical cations were preliminarily bleached in [11] and not bleached in [9,10].…”
Section: Resultsmentioning
confidence: 86%
“…1, curve c ) have a nuclear spin of I = 0 and a total abundance of ~83.7%, whereas the radical cations containing tin with odd mass numbers (Fig. 1, curve d ) are characterized by a total natural abundance of ≈ 16.3%, close magnetic moments, and the same nuclear spin ( I = 0.5).The ESR spectra of radical cations show isotropic hyperfine coupling to three equivalent protons and anisotropic hyperfine coupling to tin nuclei with odd mass numbers ( g ⊥ = 2.043, g || = 1.989; hyperfine coupling constants of ‡ ⊥ ( radical cations stabilized in the ë 3v symmetry conformation [9][10][11] (in particular, Hasegawa et al [10] reported the following set of parameters: Sn +.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations